Counselling Needs Assessment of Students of WA Polytechnic in The Upper West Region, Ghana - Abubakar, Ayamba Iddrisu; Gyeyir, Felicio Timyang; Adangabe, Amos Amuribadek (South Asian Journal of Social Sciences and Humanities, 2022)
Individuals may seek counselling for various reasons, however, whatever the reason may be, clients seek counselling in order to be able to address certain issues they may be faced in their lives. The study is about the counselling needs of students in the Polytechnic in the Wa Municipality. The data was analysed using both descriptive (frequencies and percentages) and inferential statistics (Independent t-test and One-Way ANOVA). The findings revealed that, there were significant differences in age concerning students’ ratings and needs for guidance and counselling in services. The study revealed that, students needed guidance and counselling as there were challenged in terms of time allocation problems, inability to discuss with lecturers about their problems, coping with workload issues as well as struggling to meet deadlines. Due to the absence of guidance and counselling services, the results of the study led the researchers to the conclusion that students attending Wa Polytechnic were facing a number of challenges that need answers in order to be resolved. Based on the findings and conclusion drawn from the study is recommended that the defunct guidance and counselling unit should be revived and properly resourced for students to benefit from it.